2012
DOI: 10.1371/journal.pone.0035555
|View full text |Cite
|
Sign up to set email alerts
|

More Stable Productivity of Semi Natural Grasslands than Sown Pastures in a Seasonally Dry Climate

Abstract: In the Neotropics the predominant pathway to intensify productivity is generally thought to be to convert grasslands to sown pastures, mostly in monoculture. This article examines how above-ground net primary productivity (ANPP) in semi-natural grasslands and sown pastures in Central America respond to rainfall by: (i) assessing the relationships between ANPP and accumulated rainfall and indices of rainfall distribution, (ii) evaluating the variability of ANPP between and within seasons, and (iii) estimating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
4
22
0
2
Order By: Relevance
“…Heterogeneity in semi-arid regions is associated with variability in rainfall patterns (Augustine 2010;Sanchiriro and Wyatt 2002;Hasler et al 2005). The rainfall patterns often coincide with the effects of seasonality which in turn have an effect on the productivity of grassland pastures (Ospina et al 2012). This could explain the consistent negative slope in forage quantity from the wet season to the dry season observed in this study.…”
Section: Discussionsupporting
confidence: 62%
“…Heterogeneity in semi-arid regions is associated with variability in rainfall patterns (Augustine 2010;Sanchiriro and Wyatt 2002;Hasler et al 2005). The rainfall patterns often coincide with the effects of seasonality which in turn have an effect on the productivity of grassland pastures (Ospina et al 2012). This could explain the consistent negative slope in forage quantity from the wet season to the dry season observed in this study.…”
Section: Discussionsupporting
confidence: 62%
“…The temporal changes in grassland ANPP observed in this study follow the pattern found by Ospina et al (2012) in open grasslands in the same area. ANPP is triggered at the onset of the rains, but declines at high levels of monthly rainfall.…”
Section: Discussionsupporting
confidence: 87%
“…The dominant soil type in the studied sites was a grayish to black Vertisol, with high organic matter content in the upper horizons (8 %). The natural vegetation of the region corresponds to a transitional tropical sub-humid forest with semi-deciduous vegetation, and is referred to as a seasonally dry tropical forest (Ospina et al 2012). The land-units in the study were semi-natural grasslands with scattered trees.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations